Estratégias do capital no cerrado: reestruturação agrícola no Triângulo mineiro - Rocha, Abimael Carvalho da (2025)
The restructuring of agricultural production in the Triângulo Mineiro region, the subject of this dissertation, it was conducted under state guidance from the 1960s onwards, through various programs that aimed to change the organic composition of the capital on rural production units. In addition to building transport, energy and communication infrastructures, research and financing were also necessary. This change occurred in an international economic context of a crisis in the reproduction of value, which requires compensation for the fall in the rate of surplus value. Thus, capital that was not reproducing itself sought new spaces to reproduce itself. In Brazil, the situation is one of delayed industrialization, with agriculture as one of its pillars of support. The change occurred with an increase in constant capital in rural production units and a decrease in variable capital, aiming at the search for value through relative surplus value and a continuous increase in production. The results for the Triângulo Mineiro region were changes in production and productivity rates, changes in the way work was done in the field, and the imposition of a new crop destined for the international market, soybeans, a commodity. Concomitant with this restructuring of agricultural production, the installation of the soybean agro-industrial complex took place. The research was developed with extensive bibliographical consultation on the subject and analysis of statistical data from the IBGE Census.